Study on Gender Differences among People with Lower Limb Amputation in Indian Population on the Basis of Depression, Anxiety & Stress - Shivangi Mehra; Sarika Boora; Chitra Kataria (New Visions in Science and Technology Vol. 8, 2021)
Aims and Objectives: The present study compares the level of depression, anxiety and stress on the basis of gender differences in people with lower limb amputation in Indian population. It is critical to investigate the impact of amputation on the levels of depression, anxiety, and stress in both genders because recovery from amputation is a difficult journey. Methodology: A sample of 100 Lower Limb Amputee patients who were non-prosthetic users (n=100, n=50 Males, n=50 Females) was collected from rehabilitation unit of Indian Spinal Injuries Centre & Bhagwan Mahaveer Viklang Sahayata Samiti, New Delhi. In this study data was collected by convenient sampling technique. Depression, anxiety and stress were evaluated by Depression, Anxiety and Stress Scale - 21 Items (DASS-21). The scores of depression, anxiety and stress were evaluated to find out the gender differences among subjects with lower limb amputation. Results: Data recorded was analyzed using SPSS data analysis software. An Independent t-test was used to compare the difference among both the genders with lower limb amputation in terms of depression, anxiety and stress. There was significant difference seen among the females with higher level of depression, anxiety and stress as compared to males with lower limb amputation. Conclusion: It can be concluded that there was a gender difference in context of Depression, Anxiety and Stress in subjects with lower limb amputation among Indian population. The key findings of the study suggest that the females with lower limb amputation tend to have higher level of depression, anxiety and stress in comparison of males with lower limb amputation.